Exploring the determinants of NEET youth in Jambi Province: A socioeconomic perspective - Hardiani Hardiani; Yulmardi Yulmardi; Nyimas Dian Maisyarah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study aims to analyze: 1) the socioeconomic characteristics and NEET (Not in employment, education, or training) status of young individuals in Jambi Province; 2) the determinants influencing the NEET status of young people in Jambi Province. The data utilized in this study is derived from a survey conducted in four sample villages within Jambi Province, consisting of 200 young participants. Descriptive statistical tools, single-frequency and cross-frequency tables, and binary logit regression are employed for analysis. The findings of the study reveal that: 1) NEET youth, when compared to non-NEET youth, tend to be older, have a higher proportion of females, possess higher education levels, are more likely to be married, are predominantly non-migrants, and have fewer siblings or step-siblings; 2) The parents of NEET youth, in comparison to non-NEET youth, generally have higher incomes and predominantly belong to non-Malay ethnicities in Jambi. 3) Factors significantly impacting the categorization of youth as NEET include gender, education, marital status, and parental income.